The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2015 International Conference on Advanced Engineering Materials and Technology 2015
DOI: 10.2991/icaemt-15.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Rehabilitation of Hand Dysfunction by Cyber Glove

Abstract: Abstract. This paper presents a new method of rehabilitation workstation for hand dysfunction. It has functions as follows: hand dysfunction diagnosis, assessment of disability, physical training. With the assistance of cyber gloves as well as hand strength training devices designed by the present authors, this workstation measures the hand joints movement accurately, and assesses and trains muscle strength. The system assists physiatrists to perform clinical activities such as disability evaluation, treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Studies have shown that patients who adhere to exoskeleton rehabilitation programs experience improvement in their motor functions; adherence to these programs has been found to correlate with effective rehabilitation [18]. So long as the programs and exercises are safe, comfortable, engaging, and efficient, patients should expect improvements in performance and rehabilitation [20,21]. Research has also shown that personalized treatment based on a patient's specific needs is most effective in rehabilitating patients [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients who adhere to exoskeleton rehabilitation programs experience improvement in their motor functions; adherence to these programs has been found to correlate with effective rehabilitation [18]. So long as the programs and exercises are safe, comfortable, engaging, and efficient, patients should expect improvements in performance and rehabilitation [20,21]. Research has also shown that personalized treatment based on a patient's specific needs is most effective in rehabilitating patients [22,23].…”
Section: Introductionmentioning
confidence: 99%